ASSESSMENT OF ATTITUDES TOWARD MENTAL ILLNESS AMONG MEDICAL STUDENTS IN INDIA: A CROSS-SECTIONAL STUDY - Patel, Lav; Marathe, Neera; Singh , Sandeep; Sharma, Anshuman; Namdeo , Priyanshi; Pradhan, Murchhana (Journal of Public Health Research and Community Health Development, 2024)
Background: Positive patient care attitudes for mental illness cases must be developed in the early stages of medical education since those affected by mental illness or having some mental disorder suffer negative attitudes from other people in the community. Earlier studies identified several factors that affect medical students' attitudes toward patients with mental illnesses. Purpose: The purpose of the study was to determine the attitude of medical students toward patients of mental illness. Methods: In this cross-sectional study using convenience sampling, 3rd and 4th year medical students (220) were assessed for attitudes toward mental illness using a pretested and pre-designed questionnaire which included details of socio-demographic variables such as age, gender, year of study, personal experience with mental illness, family history of mental illness or having direct contact with mental illness cases and knowledge about mental illness. Percentage and proportion were calculated, and the chi square test was applied to assess significance of the results. Results: The factors significantly associated with medical students’ attitudes toward mental illness were age, year of study, and knowing or having direct contact with mental illness patients. Those knowing mental illness cases in their family or friends had good attitude toward such patients. Conclusion: Education and direct contact with cases of mental illness serve as intervention strategies to reduce negative attitudes associated with mental illness among medical students.